Transcriptome Analysis Highlights Defense and Signaling Pathways Mediated by Rice pi21 Gene with Partial Resistance to Magnaporthe oryzae - Zhang, Yu; Zhao, Jianhua; Li, Yali; Yuan, Zhengjie; He, Haiyan; Yang, Haihe; Qu, Haiyan; Ma, Chenyan; Qu, Shaohong (Frontiers in Plant Science, 2016)
Rice blast disease is one of the most destructive rice diseases worldwide. The pi21 gene confers partial and durable resistance to Magnaporthe oryzae. However, little is known regarding the molecular mechanisms of resistance mediated by the loss-of-function of Pi21. In this study, comparative transcriptome profiling of the Pi21-RNAi transgenic rice line and Nipponbare with M. oryzae infection at different time points (0, 12, 24, 48, and 72 hpi) were investigated using RNA sequencing. The results generated 43,222 unique genes mapped to the rice genome. In total, 1,109 differentially expressed genes (DEGs) were identified between the Pi21-RNAi line and Nipponbare with M. oryzae infection, with 103, 281, 209, 69, and 678 DEGs at 0, 12, 24, 48, and 72 hpi, respectively. Functional analysis showed that most of the DEGs were involved in metabolism, transport, signaling, and defense. Among the genes assigned to plant–pathogen interaction, we identified 43 receptor kinase genes associated with pathogen-associated molecular pattern recognition and calcium ion influx. The expression levels of brassinolide-insensitive 1, flagellin sensitive 2 and elongation factor Tu receptor, ethylene (ET) biosynthesis and signaling genes, were higher in the Pi21-RNAi line than Nipponbare. This suggested that there was a more robust PTI response in Pi21-RNAi plants and that ET signaling was important to rice blast resistance. We also identified 53 transcription factor genes, including WRKY, NAC, DOF, and ERF families that show differential expression between the two genotypes. This study highlights possible candidate genes that may serve a function in the partial rice blast resistance mediated by the loss-of-function of Pi21 and increase our understanding of the molecular mechanisms involved in partial resistance against M. oryzae.